2021
DOI: 10.1186/s12891-021-04446-8
|View full text |Cite
|
Sign up to set email alerts
|

Can the body slope of interference screw affect initial stability of reconstructed anterior cruciate ligament?: An in-vitro investigation

Abstract: Background Superior biomechanical performance of tapered interference screws, compared with non-tapered screws, with reference to the anterior cruciate ligament (ACL) reconstruction process, has been reported in the literature. However, the effect of tapered interference screw’s body slope on the initial stability of ACL is poorly understood. Thus, the main goal of this study was to investigate the effect of the interference screw’s body slope on the initial stability of the reconstructed ACL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Wang JH et al noted that interference screws containing β-tricalcium phosphate, which reduced TE near the screws compared with pure poly-L-lactic acid (PLLA) screw [ 39 ]. Agarwal S et al found that a higher slope tapered interference screw could cause less damage to graft fibers, reducing graft laxity and increasing fixation stability compared to a low slope tapered interference screw [ 40 ]. However, it remains unclear whether the relative position between interference screw and graft can affect TE.…”
Section: Discussionmentioning
confidence: 99%
“…Wang JH et al noted that interference screws containing β-tricalcium phosphate, which reduced TE near the screws compared with pure poly-L-lactic acid (PLLA) screw [ 39 ]. Agarwal S et al found that a higher slope tapered interference screw could cause less damage to graft fibers, reducing graft laxity and increasing fixation stability compared to a low slope tapered interference screw [ 40 ]. However, it remains unclear whether the relative position between interference screw and graft can affect TE.…”
Section: Discussionmentioning
confidence: 99%
“…Daneshvarhashjin et al [ 12 ] investigated the effect of the body slope profile of the interference screw on the initial stability of the ACL reconstruction and suggested (1) avoiding high contact pressure from the tip to one-third of its length, and (2) a proper graft fitting is essential in the last two-thirds of the screw length since major graft slippage occurs in this region. Moreover, a tunnel diameter equal to or 1 mm larger than the screw diameter provides a better fixation compared to a 1 mm smaller tunnel diameter [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results found differences in fixation performance, but they were not statistically significant [ 10 ]. However, Athwal et al showed that screw tip design has an influence on the fixation performance [ 11 ], and the study of the IS body slope showed that it also influenced the fixation strength [ 12 ]. The use of a permanent metal IS has some disadvantages, including graft damage, tunnel widening, imaging modalities, required implant removal surgery, and increased difficulty in revision surgeries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various techniques in ACL reconstruction, using interference screw is the gold standard technique [ 7 , 8 ]{Sarzaeem, 2014 #392}. In this technique, different types of grafts could be used as a substitute for a torn ACL.…”
Section: Introductionmentioning
confidence: 99%